Drought tolerance phenotyping in sunflower inbred lines (Helianthus annuus var. macrocarpus (DC) Cockerell) - Grandon, Nancy Gabriela (2018)
Sunflower (Helianthus annuus var. macrocarpus) is the fourth most important sources of vegetable oil in the world and the second most important in Argentina. In the last years, the crop moved to marginal areas due to extension of soybean cultivation. The most important limitation of this area are the low rainfall and drought period, which affects the crop yield. In this way, in latest years, different studies were done with accessions from the Sunflower Germplasm Bank of Manfredi Experimental Station of Instituto Nacional de Tecnología Agropecuaria (INTA), to obtain a better knowledge about drought tolerance in sunflower.